2019
DOI: 10.1111/bcpt.13221
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐dependent cytokine responses of silica nanoparticles and role of ROS in human lung epithelial cells

Abstract: Reactive oxygen species (ROS) is regarded as a critical denominator in nanoparticle toxicology and inflammation. Previously, we have shown that silica nanoparticles sized 50 nm (Si50) induce release of CXCL8 and IL‐6 from BEAS‐2B cells, via mechanisms involving NFκB, p38 MAP kinase and TGF‐α‐activated EGF receptor. In the present study, the role of ROS‐mediated mechanisms in the concentration‐dependent Si50 induction of CXCL8 and IL‐6 responses was examined. Si50 (200 µg/mL) induced a time‐dependent ROS format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…This is consistent with the results of cell toxicity (Fig. 3A), as ROS is often regarded as a key factor in toxicity (37,38).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results of cell toxicity (Fig. 3A), as ROS is often regarded as a key factor in toxicity (37,38).…”
Section: Discussionsupporting
confidence: 92%
“…Both types of particles induce cytotoxic, genotoxic and pro-inflammatory acute responses [1,4,8]. In previous studies we have investigated SiNP-induced cytotoxicity, cytokine gene expression and release as well as underlying signalling pathways involved, in lung epithelial cells and macrophages in mono-cultures [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, oxidative stress caused by NMs has garnered increasing attention [ 51 , 52 , 53 ]. In particular, the role that oxidative stress plays in the organs damage caused by NMs has aroused considerate concerns by many researchers [ 54 , 55 , 56 ]. In the present study, CZON was found to potentially cause the oxidative stress to the liver and lung tissues, indicating that the liver and lung might be the major target organs of CZON after intravenous injection.…”
Section: Discussionmentioning
confidence: 99%